Smartphone use by dental students during the COVID-19 pandemic - Mezarina Mendoza , Jhon Paul Iakov (2021)
Emerging mobile apps can become very useful tools to complement virtual classes. However, all its advantages are not yet being exploited, because there is no established strategy design on how to articulate these technologies in education. Objective: To determine the use of mobile phones by dental students in pandemic times. Methods: The research design was descriptive and cross-sectional. It was made up of incoming students from 2015 to 2020 from the Faculty of Dentistry of the Universidad Nacional Mayor de San Marcos. With a 95 % confidence interval, 205 students who had a smartphone and an internet connection were selected to answer the survey. Results: 83.9 % of the students installed mobile applications. The most frequent activities were music managers (82.4 %), entertainment (66.3 %), educational games (40.5 %) and videoconferences (37.1 %). One (26.3 %) or no teachers (25.4 %) used mobile applications as a methodology tool. However, a good perception of the use of mobile apps is evidenced, with 73.7 % of students agreeing with their incorporation. Conclusion: The frequency of use and the high acceptance of use promote the implementation of applications in a complementary way to university education. Institutions should promote its use by training teachers and students on the choice and promotion of apps.